Revalidation and expanded description of Mustela aistoodonnivalis (Mustelidae: Carnivora) based on a multigene phylogeny and morphology. Issue 4 (18th April 2023) - Liu, Yingxun; Pu, Yingting; Chen, Shunde; Wang, Xuming; Murphy, Robert W.; Wang, Xin; Liao, Rui; Tang, Keyi; Yue, Bisong; Liu, Shaoying
Abstract: The lacked‐teeth pygmy weasel, Mustela aistoodonnivalis Wu & Kao, 1991, was originally described as being from Taibai Mountain and Zhashui county, Shaanxi, China. Subsequently, it was considered a subspecies or synonym of Mustela nivalis . In a faunal survey of northwestern Sichuan, eight specimens of M. aistoodonnivalis were collected. A molecular phylogenetic analysis of one mitochondrial and six nuclear genes clustered the specimens as a distinct clade and not with M. nivalis . Morphologically, the lack of the second lower molar differentiated them from M. nivalis, and genetic distances were typical of discrete species. These analyses confirmed that M. aistoodonnivalis is an independent species in the genus Mustela . Abstract : The taxonomic status of Mustela aistoodonnivalis is of great importance to the study of ecosystem. In this study, we determined the taxonomic status of M. aistoodonnivalis as an independent species through morphological and molecular biological studies and gave a detailed morphological description of M. aistoodonnivalis .